A quest for institutional foundations towards inclusive development in Sub-Saharan Africa - Machiko Nissanke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The paper explores the paths towards building institutional foundations for inclusive development in Sub-Saharan Africa. Viewing institutional configurations as a system of multiple equilibria, the concepts of endogenous institutions and institutional changes are used to address the question of how to build institutional foundations on a self-sustained basis. The paper discusses how institutional configurations have been shaped in Sub-Saharan Africa under prevailing domestic and international conditions. A resulting negative feedbacks loop in public-private interfaces has been detrimental to inclusive development. To overcome this, a strong coalition between governments and stakeholders should be developed as a social contract embedded in the taxation-public goods provision nexus.
Keywords: O43; O55; P43; P48; 330; African economies; inclusive development; institutions; institutional changes; public-private interfaces